Exploring the Phytochemistry and Pharmacological Potentials of Annona squamosa L. : A Systematic Review of Traditional Uses and Modern Applications - Muhammad Ainur Rosyid Ridho; Ratri Dwi Indriani; Arfiana Tanti Wulansari; Kristanti Indah Purwani; Tutik Nurhidayati; Indah Trisnawati; Veranita Aprilia; Anindhita Nabilah Pradani; Roy Ardiansyah Putra; Vanela Chatrin Lekatompessy (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2025)
Annona squamosa L. (Annonaceae) is a tropical evergreen fruit tree with a long history of traditional use across various cultures. Its fruit, known as srikayas, is commonly consumed fresh and used in candies, ice creams, and beverages. Different parts of A. squamosa have been widely applied in ethnomedicine as tonics, apophlegmatisants, coolants, abortifacients, and heart sedatives. Phytochemical studies have identified key bioactive compounds including annonaceous acetogenins (ACGs), diterpenes (DITs), alkaloids (ALKs), and cyclopeptides (CPs), with 33 diterpenes, 19 alkaloids, 88 acetogenins, and 13 cyclopeptides reported up to 2016. Extensive research reveals A. squamosa exhibits diverse pharmacological activities such as anticancer, antioxidant, antidiabetic, antihypertensive, hepatoprotective, antiparasitic, antimalarial, insecticidal, microbicidal, and molluscicidal effects. Notably, diterpenes and acetogenins contribute to its potent anticancer properties through apoptosis induction and cell cycle arrest. Leaf and seed extracts demonstrate significant antidiabetic, anti-inflammatory, and hepatoprotective actions, while seed peptides exhibit vasorelaxant and hypotensive effects via calcium channel inhibition. This review integrates phytochemical, ethnopharmacological, and bioactivity data, highlighting the therapeutic potential of A. squamosa and encouraging further clinical studies to validate its medicinal applications.